$Q(x,y,z)=(y′\vee z′ \vee 0\vee x′)\wedge1\wedge(z\vee x′\vee 0\vee y\vee z)′\wedge(z′\vee x\vee y\vee z′)$

I'm not supposed to use tables but only proprieties like De Morgan ecc.

EDIT: So I simplyfied and reordered using commutativuty, identity and idempotent laws. Now I have this expression:

$Q(x,y,z)=(x′\vee y′ \vee z′)\wedge(x\wedge y'\wedge z')\wedge(x\vee y\vee z′)$

Think I should bring it in a sum of product form but I'm not sure how.


$Q(x,y,z)=(\neg y\vee \neg z \vee 0\vee \neg x)\wedge1\wedge \neg (z\vee \neg x\vee 0\vee y\vee z) \wedge(\neg z\vee x\vee y\vee \neg z)$

You need:

  • Identity Law: $A \vee 0 = A$ and $A \wedge 1 = A$.
  • Idempotent Law: $A \wedge A = A$.
  • deMorgans: $\neg(A \vee B) = \neg A \wedge \neg B$

Use this to get you started. You will need Distributive to simplify.

Edit your question to show what you have attempted. Someone will help if you demonstrate a willingness to try.


$Q(x,y,z)=(\neg y\vee \neg z \vee \neg x)\wedge (x\wedge \neg y \wedge \neg z) \wedge(x\vee y\vee \neg z)$

$Q(x,y,z)=(\neg y\vee \neg z \vee \neg x)\wedge x\wedge \neg y \wedge \neg z \wedge(x\vee y\vee \neg z)$

Now, look for common factors (Distributive: $A \wedge (B \vee C) = (A \vee C) \wedge (A \vee C)$, and use Annulment $A \wedge 1 = A$.

Hint: factor out $x$ or $\neg y$ or $\neg z$. $A \wedge (A \vee B) = A \vee (1 \wedge B) = A$

Again, edit your question. Someone will verify. (And they do get easier...)

Laws and Theorems of Boolean Algebra


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.